(3HGH HjGf Yed jhe hdjdI ddCHQGQ hYed jhe hSjdI GdeSGjQjf Edi WQjb GdebQHjfs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3EYde habfG Gddg hEjGc deG jMHg efG hjQVGg Cf GdCHQGQ ge GdJhGHhf EPG EfJghG ef efGege EgJehG HEbGeI CeQ Gddg YR hLd ef GdhVhA hGdUdGI s
(3BNQgG (B:s
(3hai GdLedI aeG PcQ dc LedI MGdge ge bhe bO MTG bdhHge CfhGQ hLhOg GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG hMHjHfG hTajYfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs